Cognitive Approach to “Diary of an African Man Wearing a Floral Shirt and Smoking LM in the Time of the Revolution” by Khaled Ben Salah - ghilous, salah (El Omda in Linguistics and Discourse Analysis, 2023)
The cognitive approach to language stems from the principle that language is an accurate and representative reflection of the general mental ability of humans, as it relates to the process of determining the specificity of the linguistic discourse. On the one hand, it presupposes a complex conceptual ground that includes things such as the cognitive background and the awareness of the physical, social and linguistic context, and on the other hand, a statement imposes that a specific one reflects only one of the ways that are not limited to the perception of the situation in question and its depiction in the discourse.